The Dynamics of the Bioclimatic Indices of Environmental Comfort in the Udmurt Republic, Russia - Yu.P. Perevedentsev; A.V. Shumikhina (Учёные записки Казанского университета: Серия Естественные науки, 2016)
This paper provides a review of the biometeorological indices used to assess the degree of comfort of weather and climate conditions. Statistical calculations of the effective and equivalent effective temperature have been performed for eight weather stations in the Udmurt Republic (Russia) during the period of 1961–2014. The effect of varying weather conditions on the functional state of the human body has been revealed based on the indices of weather hardness and pathogenicity. It has been found that the weather conditions in the region of study are comfortable only in the summer period. In the winter period, they are either irritating or acute. Positive values of the coefficients of linear trend inclination prevail for most biometeorological indices, thereby showing that the weather conditions improved over the last decades. Sample calculations of the biometeorological indices have been given for the extreme weather situations.